2010
DOI: 10.1002/anie.201005511
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Electron Uranyl Reduction by a Rare‐Earth Cation

Abstract: Unlike their transition-metal analogues, the oxo groups of the uranyl dication, [UO 2 ] 2+ , which has a linear geometry and short, strong UÀO bonds are commonly considered inert. [1] Very little Lewis base character has been demonstrated for the uranyl oxo groups, [2,3] which makes them poor models for the heavier, highly radioactive transuranic actinyl cations such as neptunyl [NpO 2 ] n+ (n = 1, 2). [4,5] The heavier actinyls are important components in nuclear waste and demonstrate oxo basicity that can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
93
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 35 publications
7
93
1
Order By: Relevance
“…The X-ray crystallographic analyses for the series of compounds 2-Ln showed that they are all dimers in the solid state with the asymmetric unit containing two similar molecules of diamond-shaped UO 2 dimers in most cases ( Figure 1). They are isostructural to [{UO 2 Ln(py) 2 (L)} 2 ] (M = Sm, Y), both of which were previously communicated by us, 19 in which both the uranium and lanthanide centers are seven-coordinate with approximate pentagonal bipyramidal geometry but with a greater distortion at the lanthanide. Four equatorial N atoms from the N 4 -donor set of the macrocycle contribute to each metal coordination sphere.…”
Section: Synthesis Of the Dimericmentioning
confidence: 95%
See 1 more Smart Citation
“…The X-ray crystallographic analyses for the series of compounds 2-Ln showed that they are all dimers in the solid state with the asymmetric unit containing two similar molecules of diamond-shaped UO 2 dimers in most cases ( Figure 1). They are isostructural to [{UO 2 Ln(py) 2 (L)} 2 ] (M = Sm, Y), both of which were previously communicated by us, 19 in which both the uranium and lanthanide centers are seven-coordinate with approximate pentagonal bipyramidal geometry but with a greater distortion at the lanthanide. Four equatorial N atoms from the N 4 -donor set of the macrocycle contribute to each metal coordination sphere.…”
Section: Synthesis Of the Dimericmentioning
confidence: 95%
“…19 First, we fitted the d.c. magnetic susceptibility measured for 3-Li at different values of the applied magnetic field by diagonalizing the Zeeman Hamiltonian…”
Section: Synthesis Of the Dimericmentioning
confidence: 99%
“…[1,2] For example, new routes to the singly reduced, pentavalent uranyl have been developed and have facilitated fascinating new Lewis acidbase interactions between the oxo groups and alkali metals, [3,4] boranes, [5][6][7] transition metals, [8] rare earth metals, [9] and other uranyl cations. [10] In some cases it is evident that oxo group functionalization can modify the U VI / U V reduction potential such that reduction is facilitated.…”
mentioning
confidence: 99%
“…
The chemical reactivity of the oxo group of the uranyl dication, [UO 2 ] 2+ , the most prevalent aqueous and environmental form of uranium and by far the most chemically inert, has been transformed in recent years. [1,2] For example, new routes to the singly reduced, pentavalent uranyl have been developed and have facilitated fascinating new Lewis acidbase interactions between the oxo groups and alkali metals, [3, 4] boranes, [5][6][7] transition metals, [8] rare earth metals, [9] and other uranyl cations. [10] In some cases it is evident that oxo group functionalization can modify the U VI / U V reduction potential such that reduction is facilitated.
…”
mentioning
confidence: 99%
“…Pentavalent uranium seems to retain its Ising ground state, and one U V -Sm III complex displays a very strong superexchange coupling between the 5f 1 and the 4f 5 centers, which may sound surprising because of the largely reduced radial extent of the 4f shell (with respect to 5f and especially 3d) but might perhaps be explained considering the relative instability of the pentavalent state of uranium and the close divalent state of samarium. [18] Conversely, the dimeric (U V -Dy III ) 2 complex exhibits a butterfly-shaped hysteresis cycle, behaving as a SMM up to 3 K. [19] The , so that the dominant exchange interaction, albeit antiferromagnetic, actually favors a "parallel" alignment of their two spins. [20] The 5f 3 Configuration: U III , Np…”
Section: VImentioning
confidence: 99%